Text and Image: Friendship, Unconstraint, and Life Philosophy in Shi Tao’s Drunk in Autumn Woods - Rongqiao, Wu (Sinología hispánica. China Studies Review, 2024)
In Chinese cultural tradition, there is an affectionate bond between man and nature. In the eyes of the ancients, everything in the world has vitality. This kind of Life Philosophy consideration, as a lofty aesthetic principle, not only guides artistic activities but also shapes the Chinese national characteristic. This article attempts to inquire into the humanistic spirit of Chinese landscape painting in the light of Life Philosophy. Through a semiotic and socio-cultural analysis of Shi Tao’s Drunk in Autumn Woods (c. 1702), this paper aims to discover the expressive strategies for the representation of drunkenness in the autumn forest on the other hand, to inquire into the ultimate concern behind the artistic signs on the other hand. In this way, it also invites us to reflect on a new hermeneutic path different from stylistics and iconology to understand the Literati Painting.